First measurement of the surface tension of a liquid scintillator based on Linear Alkylbenzene (HYBLENE 113). (1st May 2022) - ,; Alt, J.; Arutinov, D.; Bezshyyko, O.; Bretz, T.; Brignoli, A.; Conaboy, A.; Deucher, P.; De Paola, F.; del Giudice, G.; di Cristo, C.; Fecarotta, O.; et al.
Abstract: We measured the surface tension of linear alkylbenzene (LAB) HYBLENE 113 mixed with Diphenyloxazole (PPO) as well as of pure LAB HYBLENE 113 as part of material studies for the liquid-scintillator based surround background tagger (SBT) in the proposed SHiP experiment. The measurement was performed using the iron wire method and the surface tension for linear alkyl benzene HYBLENE 113 plus PPO was found to be (30.0 ± 0.6) mN/m 22.0 ± 0.5°C and for pure HYBLENE 113, (29.2 ± 0.6) mN/m at 21.0 ± 0.5°C.